HOLDING GAINS ON FIXED ASSETS: AN ELEMENT OF BUSINESS INCOME? - Dikens, Robert L.; Blackburn, John O. (The Accounting Review, 1964)
The article focuses on the desirability of reporting the difference between movements of the general price level and movements in the "value" of specific assets, particularly as related to fixed assets. This difference is identified in Accounting Research Study No. 3 as "holding gains and losses" and defined as "the amount attributable to acquisition of goods or services prior to their utilization." It also presents the concept of income, which includes changes in replacement cost of fixed assets as a part of business income, even though a separately reported part, fails to serve these purposes. The failure of replacement cost as a measure of economic value of specific assets, the failure of fortuitous movements of replacement cost to qualify as an element of a useful figure to report as business income, and the possibility of substantially distorted reported income due to the leverage caused by the size of the stock of assets compared to income, coupled with the impossibility of objective measurement of replacement cost effectively condemn any concept of income proposed to date that would include holding gains or losses on fixed assets.